2022
DOI: 10.20892/j.issn.2095-3941.2022.0254
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic revolution for inoperable stage III non-small cell lung cancer in the immune era

Abstract: In the past, chemoradiotherapy (CRT) has been the standard of care for inoperable stage III NSCLC. Concurrent chemoradiotherapy (cCRT), if tolerable in patients, is the optimal treatment regimen. A meta-analysis has shown that cCRT results in a 5-year survival rate 4.5% longer than that with sequential chemoradiotherapy (sCRT) 1 . However, within 2 years after cCRT, approximately 30% of patients experience local recurrence, and approximately 40% develop distant metastasis 2 . Clinicians have explored induction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Advances in cancer immunotherapies for patients with NSCLC have led to significant improvement in survival 16 , but for patients with LS-SCLC the optimal dose-fractionation schedule of TRT remains debatable. While the Intergroup 0096 trial reported an improvement in survival for BID over QD radiotherapy patterns, traditional standard fractionation (QD) has remained the most common approach over the past decade, and is still very commonly used in the US 22 and China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in cancer immunotherapies for patients with NSCLC have led to significant improvement in survival 16 , but for patients with LS-SCLC the optimal dose-fractionation schedule of TRT remains debatable. While the Intergroup 0096 trial reported an improvement in survival for BID over QD radiotherapy patterns, traditional standard fractionation (QD) has remained the most common approach over the past decade, and is still very commonly used in the US 22 and China.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that different radiation doses are required to control clinical and subclinical lesions, and 50 Gy is an optimal dose for subclinical lesions 14 . Furthermore, immunotherapy has an increasingly important role in comprehensive treatment, and a combination of immune checkpoint inhibitors (ICIs) and TRT requires fewer radiation-related toxicities 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Research concerning anticancer drugs for SCLC is significantly less common than that for NSCLC [ 11 , 17 , 18 ]. Treatment progression for SCLC has remained largely unchanged over the past 20 years, generally comprising 4–6 cycles of chemotherapy with cisplatin and etoposide, RT, and prophylactic cranial irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Defective immune cell function coupled with immunosuppressive factors in the tumor microenvironment (TME) results in cancer cells that evade recognition and destruction in patient with lung cancer. Given that patients with low tumor immune escape have a longer disease-free survival (DFS) 1 , immune checkpoint inhibitors (ICIs) have achieved long-term survival in patients with advanced non-small cell lung cancer (NSCLC) 2 and inoperable stage III NSCLC 3 . However, a significant number of patients do not respond to therapy or rapidly develop drug resistance 4,5 .…”
Section: Introductionmentioning
confidence: 99%